2015
DOI: 10.1016/j.arabjc.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A review on sample preparation and chromatographic determination of acephate and methamidophos in different samples

Abstract: Acephate and its metabolite methamidophos are common organophosphorus insecticide used for crop protection. High uses of acephate and methamidophos have induced health issues and environmental pollution. Their undesired presence in the environment is creating ecotoxicology and may harm human health. It is therefore essential to detect the presence of acephate and methamidophos even in trace level. In this review, we have tried to accommodate successful methods of detection of acephate and methamidophos in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…Heavy metals contamination is the result of technological development, occurring at significant concentrations in the environment (Barakat 2011;Kishe and Machiwa 2003). Because of the environmental persistence, toxicity and ability to be incorporated into food chains, these industrial wastes including heavy metal are new threat and challenge (Forstner and Wittman 1983;Kumar et al 2015a;Machiwa 1992). Same time, the pollution sources of heavy metals in environment are mainly derived from anthropogenic sources include mining, smelting, waste disposal, urban effluent, vehicle exhausts, sewage sludge, pesticides, fertilizers application (Kim et al 1998;Kumar et al 2013aKumar et al , b, 2015bPrasad et al 2013;Wei and Yang 2010).…”
mentioning
confidence: 99%
“…Heavy metals contamination is the result of technological development, occurring at significant concentrations in the environment (Barakat 2011;Kishe and Machiwa 2003). Because of the environmental persistence, toxicity and ability to be incorporated into food chains, these industrial wastes including heavy metal are new threat and challenge (Forstner and Wittman 1983;Kumar et al 2015a;Machiwa 1992). Same time, the pollution sources of heavy metals in environment are mainly derived from anthropogenic sources include mining, smelting, waste disposal, urban effluent, vehicle exhausts, sewage sludge, pesticides, fertilizers application (Kim et al 1998;Kumar et al 2013aKumar et al , b, 2015bPrasad et al 2013;Wei and Yang 2010).…”
mentioning
confidence: 99%
“…Recent studies have revealed that hydrolysis of molecules 1-3 is very slow in water, and half life increases up to tenfold [28][29][30][31]. The slow decomposition was attributed to the formation of the six-membered ring through H association (Figure 1).…”
Section: Effect Of Ph Variation On Titled Moleculesmentioning
confidence: 99%
“…Moreover, the acid dissociation constant (pKa values) has a direct relationship with pH values, so pKa values can play a significant role in decomposition (thermally, chemically and biochemically), persistence and reactivity of molecules [28][29][30][31][32][33]. The pKa values depend upon the number of dissociated hydrogen ions, and it is directly proportional to the stability of the molecule (ΔG = 2.303 RT pKa).…”
Section: Effect Of Ph Variation On Titled Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides are integral part of modern agriculture (David, 1998; Chen et al, 2014), which increased tremendous chemical pressure on agricultural soil and in turn has affected entire ecosystem (Karpouzas et al, 2014; Kumar et al, 2015c; Kienzler et al, 2016; Rivera-Becerril et al, 2017). Environmental Protection Agencies (Gallegos Saliner et al, 2006; Balderacchi et al, 2014) are very cautious and place several checks before passing any chemical to act as a pesticide (Krupadam et al, 2003; Gallegos-Saliner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%